Increasing prevalence of antimicrobial resistance in urinary tract infections of neurological patients, Seoul, South Korea, 2007–2016. (July 2019) - Shin, Hye-Rim; Moon, Jangsup; Lee, Han Sang; Ahn, Seon Jae; Kim, Tae-Joon; Jun, Jin-Sun; Sunwoo, Jun-Sang; Lee, Soon-Tae; Jung, Keun-Hwa; Park, Kyung-Il; Jung, Ki-Young; Kim, Manho; et al.
Graphical abstract: Highlights: The most common pathogen in UTI was Klebsiella pneumonia, followed by Escherichia coli, and Enterococcus species. In catheter-associated UTI, the most common pathogen was Enterococcus species. The susceptibilities to ciprofloxacin, ceftazidime, and piperacillin/tazobactam have decreased in UTI-associated pathogens over ten years. The proportion of ESBL-producing pathogens increased in UTIs associated with Klebsiella pneumoniae. However, MDR in K. pneumoniae, ESBL-producing E.coli, and MDR in E.coli were did not change significantly. Abstract: Objectives: Urinary tract infection (UTI) is a common medical complication experienced by patients with neurologic diseases. In this study, we established the microbial etiologies of UTI, and resistances to antibiotics in UTI as well as determining which appropriate empirical antibiotics should be used to treat UTI in neurological patients. Designs and methods: We retrospectively reviewed microbial etiologies and antimicrobial resistance among patients experiencing UTI events in the neurology ward of Seoul National University Hospital from 2007 to 2016. Results: The total number of UTI events observed was 301, and Klebsiella pneumoniae was the most common pathogen observed in UTIs. But in catheter-associated UTI (CAUTI), Enterococcus species were the most prevalent pathogens. Susceptibility to commonly-prescribed antibiotics decreased over 10 years, indicating increased antibiotic resistance in pathogens associated with UTI. ESBL-producing K. pneumoniae increased significantly, while increases of MDR K. pneumoniae, ESBL-producing E. coli, and VRE were not observed. Conclusions: The worldwide trend of increasing drug-resistant pathogens should be considered, and further studies on antibiotics resistance in UTI are needed. These data will greatly assist physicians when they select antibiotics to treat UTIs in neurological patients.